LEADERSHIP/ MANAGEMENT CHALLENGES OF SECONDARY SCHOOLS IN WOLAITA AND DAWRO ZONES, SOUTH ETHIOPIA - Labiso, Tafano Ouke; Demissie, Endale Berhanu; Kebede, Deribe Debella (Advances in Social Sciences Research Journal, 2019)
The purpose of this study was to analyze the major leadership challenges of the secondary schools of Dawro and Wolaita zones. In order to attain this objective descriptive survey method was employed. The study was carried out in four general secondary schools of wolaita and Dawro zones. Stratified sampling technique for the selection of the schools, simple random sampling technique for teachers’ selection and availability for principals’ selection were used. Hence, principals and teachers were involved and the questionnaire was distributed among teachers and principals and again principals were interviewed. And, also the three years’ (2002-2004 E .C.) EGSECE performance document was analyzed. The data gathered through questionnaire were analyzed using percentages and average mean. Based on the analysis, the study disclosed that the input, competency, economic, social, and attitudinal factors were found to be the major challenges. Accordingly, it was concluded that the challenges were multifaceted. Hence, it is recommended that all the concerned bodies of the zones should take measures to improve the performance of students through tackling the problems taking into account that the outputs of this level are the inputs for the current 33 universities and different development sectors of the country. Key words: Leadership, Leadership Challenges, Secondary Schools, Principals, Student Performance, Management